One of the isoamylase isoforms, CMI294C, is required for semi-amylopectin synthesis in the rhodophyte Cyanidioschyzon merolae - Maeno, Toshiki; Yamakawa, Yuki; Takiyasu, Yohei; Miyauchi, Hiroki; Nakamura, Yasunori; Ono, Masami; Ozaki, Noriaki; Utsumi, Yoshinori; Cenci, Ugo; Colleoni, Christophe; Ball, Steven; Tsuzuki, Mikio; et al. (Frontiers in Plant Science, 2022)
Most rhodophytes synthesize semi-amylopectin as a storage polysaccharide, whereas some species in the most primitive class (Cyanidiophyceae) make glycogen. To know the roles of isoamylases in semi-amylopectin synthesis, we investigated the effects of isoamylase gene (CMI294C and CMS197C)- deficiencies on semi-amylopectin molecular structure and starch granule morphology in Cyanidioschyzon merolae (Cyanidiophyceae). Semi-amylopectin content in a CMS197C-disruption mutant (ΔCMS197C) was not significantly different from that in the control strain, while that in a CMI294C-disruption mutant (ΔCMI294C) was much lower than those in the control strain, suggesting that CMI294C is essential for semi-amylopectin synthesis. Scanning electron microscopy showed that the ΔCMI294C strain contained smaller starch granules, while the ΔCMS197C strain had normal size, but donut-shaped granules, unlike those of the control strain. Although the chain length distribution of starch from the control strain displayed a semi-amylopectin pattern with a peak around degree of polymerization (DP) 11-13, differences in chain length profiles revealed that the ΔCMS197C strain has more short chains (DP of 3 and 4) than the control strain, while the ΔCMI294C strain has more long chains (DP >12). These findings suggest that CMI294C-type isoamylase, which can debranch a wide range of chains, probably plays an important role in semi-amylopectin synthesis unique in the Rhodophyta.